Penerapan Terapi Musik Terhadap Penurunan Tingkat Halusinasi Pendengaran pada Pasien Gangguan Jiwa di Rumah Sakit Jiwa RSJD Dr. RM Soedjarwadi Klaten Provinsi Jawa Tengah - Anis Anggoro Wati; Sitti Rahma Soleman; Wahyu Reknoningsih (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Hallucinations are one of the symptoms of mental disorders in which the patient experiences changes in sensory perception, feels false sensations in the form of sound or without real stimulation. One way to reduce the impact of auditory hallucinations is by providing music therapy. Purpose To find out the results of the implementation of the application of music therapy to the level of auditory hallucinations at Rsjd Dr. RM. Soedjarwadi, Central Java Province. Methods The research design was conducted on 2 female respondents by way of pretest posttest with the action of Mozart music therapy for 10-15 minutes and using interviews and providing AHRS observation sheets. The results of 2 respondents before music therapy were in severe auditory hallucinations, namely Mrs.S with a score of 24 and Mrs. SR 27. Then the auditory hallucinations of 2 respondents after music therapy were in mild and moderate hallucinations with a score of Mrs.S 7 and Ny. Sr 12. There are differences in the development of respondents with auditory hallucinations before and after the music therapy intervention. Conclusion There are differences in development before and after music therapy is carried out in hallucinatory patients.